Implementasi Digital Literasi dengan Menggunakan Aplikasi Canva dalam Pembuatan Buku Cerita Digital Pada Guru PAUD: Implementation of Digital Literacy Using the Canva Application in Making Digital Story Books for PAUD Teachers - Fatimah; Hasiana, Isabella (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
The purpose of this study was to determine the implementation of digital literacy in Early Childhood Education. Teachers through the use of Canva application in making digital storybooks. The participants in this study were teachers in kindergartens in Waru sub-district, Sidoarjo. Data analysis used experimental quantitative statistical methods to compare differences between experimental and control groups. The results of the study are expected to provide insight into the improvement of digital literacy skills of early childhood teachers, the effectiveness of digital storybooks in improving early childhood children's concept understanding, and the collaborative impact of using technology in early childhood learning. The evaluation results show that digital storybooks created using Canva have a much higher visual and interactive appeal than conventional storybooks. On digital skills improvement, the t-test results showed a significant increase (p<0.05) in digital literacy skills in the experimental group after the training using Canva. The percentage of preschool children who liked digital storybooks reached 85%. Preschool children who interacted with digital storybooks showed a significant increase in concept understanding. ABSTRAK Tujuan penelitian ini untuk mengetahui implementasi digital literasi pada Guru PAUD melalui penggunaan aplikasi Canva dalam pembuatan buku cerita digital. Partisipan dalam penelitian ini adalah guru di TK di Kecamatan Waru, Sidoarjo. Analisis data menggunakan metode statistik kuantitatif eksperimen untuk membandingkan perbedaan antara kelompok eksperimen dan kontrol. Hasil penelitian diharapkan dapat memberikan wawasan tentang peningkatan keterampilan digital literasi guru PAUD, efektivitas buku cerita digital dalam meningkatkan pemahaman konsep anak-anak PAUD, dan dampak kolaboratif dalam penggunaan teknologi dalam pembelajaran anak usia dini. Hasil evaluasi menunjukkan bahwa buku cerita digital yang dibuat dengan menggunakan Canva memiliki daya tarik visual dan interaktif yang jauh lebih tinggi daripada buku cerita konvensional. Pada peningkatan keterampilan digital hasil uji t menunjukkan peningkatan signifikan (p<0.05) dalam keterampilan digital literasi pada kelompok eksperimen setelah pelatihan menggunakan Canva. Persentase anak-anak PAUD yang menyukai buku cerita digital mencapai 85%. Anak-anak PAUD yang berinteraksi dengan buku cerita digital menunjukkan peningkatan pemahaman konsep yang signifikan.